Level of faecal contamination in vegetables sold in the Huanuco markets and their relationship in wastewater irrigation untreated - Escobedo Bailon, Christian Michael (2017)
Objetive. To determine the level of faecal contamination in vegetables sold in the Huánuco marketsand their relationship in wastewater irrigation untreated.Methods. Was designe an correlational study, with 84 vegetables samples corresponding to theHuánuco markets and also 84 irrigation water samples of the vegetables in study, during 2014. Thedata were obtained by laboratory tests and observation guides. Th determination of E. coli was madefor the membrane filter method. Was performed an bivariate analysis through the chi square test.Results. The prevalence of E. coli was 34,5%(29/84). The chinese chives showed higher prevalenceof contamination, continued of coriander, parsley and radish. Were found statistically significantassociations (P≤0,05) among the contamination irrigation wáter and the prevalence of E. coli in thevegetables as chinese chives, coriander, parsley and radish.Conclusions. The prevalence of E. coli in the vegetables were high and relate with the fecalcontamination of irrigation wáter.